A critical review on society’s perception on the usage of mosque - Norman Shah, Muhammad Nazrin Shah; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Mohd Ariffin, Noor Fazamimah (INSInet Publication, 2015)
The uses or functions of mosques in the modern era has significantly evolved through the years since the very first mosque ever was built by the Prophet Muhammad (pbuh). The spread of Islam throughout the world results in the different adaptation or representation of Islam in terms of architecture and symbolism of the religion. The result of evolution of the uses and the architectural symbolism of the mosques creates a stereotypical thinking of current local societies of what mosques are all about. Back in the days, the mosque was a place for the local society to connect to one another, held religious activities and other activities related to the local community. The mosque of Prophet Muhammad (pbuh) does not emphasize on the aesthetical values but emphasize more on the function and needs of the local society. Mosques in the modern era emphasizes more on the aesthetical values and grandness rather than the function and needs of the local society. The main objective of this research is to identify what are the dominant factors that affect the stereotypical thinking of local society towards the usage of the mosque and how does the aesthetic values give impacts to the thinking of the local society.